A Comparison of Cefazolin Versus Ceftriaxone for the Treatment of Methicillin-Susceptible Staphylococcus aureus Bacteremia in a Tertiary Care VA Medical Center. (18th May 2018) - Carr, Dustin R; Stiefel, Usha; Bonomo, Robert A; Burant, Christopher J; Sims, Sharanie V
Abstract: Background: Cefazolin and ceftriaxone are frequently used to treat methicillin-susceptible Staphylococcus aureus (MSSA) bacteremia, especially in the realm of outpatient parenteral antimicrobial therapy. Both antimicrobials have been associated with favorable clinical outcomes for mixed MSSA infections. However, limited published data exist specifically comparing the use of these agents for the treatment of MSSA bacteremia. Methods: We conducted a retrospective cohort study of Veteran patients with MSSA bacteremia who received ≥14 days of cefazolin or ceftriaxone between 2009 and 2014. Rates of treatment failure were compared between both groups. Treatment failure was defined as therapy extension, incomplete therapy, unplanned oral suppressive therapy, relapse of infection, or hospital admission or surgery within 90 days. Results: Out of 71 patients, 38 received treatment with cefazolin and 33 with ceftriaxone. The overall rate of treatment failure was 40.8%, with significantly more failures among patients receiving ceftriaxone (54.5% versus 28.9%; P = .029). Factors associated with treatment failure included longer duration of parenteral therapy, heart failure, and treatment in an external skilled nursing facility as compared with treatment in the Department of Veterans Affairs attached Community Living Center. Conclusions: Ceftriaxone had a higher rate of treatment failure than cefazolin for the treatment of MSSA bacteremia in a Veteran population. Potential reasons for this could include the higher protein binding of ceftriaxone, ultimately resulting in lower serum concentrations of free drug, or other unknown factors. Further studies are warranted to confirm these results.